N(CH3)(4)][(UO2)(2)F-5]: A new organically templated open- framework uranium oxide fluoride (MUF-2) - Ok, K; Doran, M; O'Hare, D (2006)
A three-dimensional open-framework uranium oxide fluoride, denoted as MUF-2 was hydrothermically synthesized and characterized. It is a three-dimensional crystal structure consisting of seven co-ordinate UO2F5 pentagonal bipyramids that are connected through fluorine atoms. It contains ten-membered ring (10-MR) channels running along the [100] and [010] directions, containing tetramethyl ammonium cations. An eight-membered ring channel also runs along the direction with appropriate dimensions of 4.0 × 4.0 A. The amount of void space was calculated by removing all of the non-framework atoms, and using the CALC SOLV command. The structural topology of MUF-2 suggested the possibility of ion-exchange reactions. Thermal analysis revealed that the material is stable up to 350 °C. It was also suggested that the stability of MUF-2 depends upon the anions and their ligating ability to the uranyl cations.